Polyfunctionality of natural killer cell in healthy donors - Wutti-In Y. (2017)
© 2016, Walailak University. All rights reserved. Background: Natural killer (NK) cells are important guards of the innate immune system, which act by performing as primary effector cells in viral infections. NK cell function is regulated by the engagement of activating and/or inhibitory receptors on individual NK cell surfaces. Subsequent to activation, the release of preformed cytolytic granules or cytokines occurs. Recently, the polyfunctionality of NK cells has been described as a potent NK cell subset that mediates antiviral response in HIV-infected slow progressors.Objectives: To evaluate the polyfunctional NK cells in healthy individuals. Methods: Peripheral blood mononuclear cells (PBMCs) were separated from 41 healthy blood donors by Ficoll-Hypaque gradient centrifugation. Multicolor flow cytometry was used to investigate the expression of function markers (degranulation marker (CD107a), IFN-γ, and TNF-α) on NK cells following PMA/Ionomycin or K562 stimulation.Results: The percentage of NK cells expressing CD107a, IFN-γ, or TNF-α in response to PMA/Ionomycin were 17.85, 10.56, and 2.66 %, respectively. The NK cells expressing CD107a, IFN-γ, or TNF-α in response to K562 stimulation were 6.43, 2.09, and 0.57 %, respectively. The capability of NK cells to perform polyfunctions was 6.19 % of the total NK cells following PMA/Ionomycin stimulation, while 1.06 % was observed following K562 stimulation. The trifunctional CD107a + / IFN-γ + / TNF-α + NK cell subset was found to be 0.95 and 0.04 % following PMA/Ionomycin and K562 stimulation, respectively. Conclusion: A small fraction of NK cells was capable of performing polyfunctions following stimulation, with less than 1 % being able to perform trifunctions in this study setting.